Technology-based multinational companies from Venezuela: application of theories in case studies (Dissertare, 2017)
This article presents two cases of technology-based companies of Venezuelan origin, which in addition to becoming internationalized, became multinationals with a regional scope. The purpose of this descriptive work is to establish which of the explanatory theories of internationalization and multinationalization processes are applicable to the analyzed cases of study. The qualitative methodology was used based on the case study. The data were obtained from the application of an interview in one of the companies and secondary sources obtained from the other. The conclusion of the study is that all the theories that explain the multinationalization of companies are applicable to the cases studied, but only the International New Ventures Model can be related to the internationalization process followed by the organizations analyzed
Keywords: multinational companies; theories; internationalization; study cases; Venezuela